Pengembangan Aplikasi Informasi Posyandu dalam Meningkatkan Layanan Kesehatan Ibu dan Anak - Nana Suarna; Nining Rahaningsih; Euis Fadilah; Farah Nur Farida (AMMA : Jurnal Pengabdian Masyarakat, 2022)
This Community Partnership Program aims to develop a Posyandu information system application to improve the efficiency and effectiveness of maternal and child health services. This application is designed to facilitate Posyandu officers in managing patient data, recording health histories, monitoring child development, and providing relevant health information. The application development includes needs analysis, user interface (UI) design, implementation of key features, and application usage training for Posyandu officers. It is expected that with this application, the quality of health services at Posyandu can be improved, and health information access for mothers and children can be facilitated.